Posterlance / Nur Irdina Abdul Ghani and Geraldine De Mello - Abdul Ghani, Nur Irdina; De Mello, Geraldine (Academy of Language Studies, 2023)
The purpose of this extended abstract is to help owners to showcase the products that they are going to release creatively using a modern application, the well-known software, Canva. This project will include selling their products specifically for business marketing. Business owners nowadays are leaning towards a more modernised marketing strategy in the form of digital posters or more commonly known amongst the younger generation as e-posters. This project showcases the amount of help that business owners are looking for when it comes to publicly marketing their products using present strategies. Posterlance will be carried out through personal encounters between the project and the business’ owners when it comes to deciding what type of posters that the clients have in mind. There will be platforms, via Whatsapp or Instagram, opened to promote this service and any further discussions with future clients will be handled through the platforms provided. Posterlance will provide the best satisfaction to its clients when it comes to a creative digital poster.